Strategies of Urban Spaces Developments Approaching Urban Events in Iranian Cities - Molaei, Asghar (Street Art & Urban Creativity, 2023)
The city is a complex and integrated reality of all social, cultural, economic, environmental, physical and other environmental factors. Designing a city that takes into account the qualitative criteria of these factors can be a creative work and creative urban spaces and the city as a work of art. In the city as an artistic phenomenon, beauty is a key feature of the city and its components. Features such as order, harmony, cohesion and consistency in the city can also be seen as works of art. Therefore, the purpose of this paper is to explain the approach of the city as a creative work of art and design as a strategy for achieving it through exploratory research and interdisciplinary research and documentary research methods and library studies. Be. The results of this research indicate that the use of urban design art is one of the most important factors in attracting tourists, investors and economic and tourism boom. Creativity in the design of public spaces, buildings and social centers can be done in a contemporary, traditional context. Public spaces, squares and streets, urban and neighborhood entrances, public places, cultural, social, pilgrimage, recreational, sports, and economic hubs in Iranian cities are among the most important areas of applying creativity to create artwork. Applying creative power and expanding it in various fields will bring to light interesting and unique phenomena in different areas and areas and will create a beautiful and artistic city. Iranian cities have many beautiful urban spaces, squares, garden alleys, museums, mosques that act as urban place brands for citizens and tourists.